Optimal configuration of arthroscopic sliding knots backed up with multiple half-hitches - Jo, Chris H.; Lee, Ji-Ho; Kang, Seung-Baik; Lee, Jae Hyup; Han, Hyuk Soo; Bae, Tae Soo; Choi, Kuiwon; Lee, Changyang; Lee, Myung Chul; Yoon, Kang-Sup (SPRINGER, 2008)
The purpose of this biomechanical study was to determine optimized configuration of additional half-hitches placed after various arthroscopic sliding knots. Four commonly used arthroscopic sliding knots, namely, the Duncan loop, the SMC, Weston, and SP knot, were included in this study. All knots were tied with a single-hole knot pusher using a knot-tying simulator. After tying a sliding knot, it was backed up with zero to four additional reverse half-hitches on alternating posts (RHAPs). The first half-hitch was either placed on the same post (conventional RHAP; c-RHAP) or on the loop limb of the sliding knot (switched RHAP; s-RHAP). Ten knots were tied in each configuration using No. 2 Ethibond or No. 1 PDSII sutures. Loop security (loop circumference at 5 N) and knot security (highest load to failure at a cross-head displacement of 3 mm) were measured. Knot configurations, number of RHAPs, or mode of placement of the first half-hitch did not make clinically significant effects on loop security for either suture type. Using No. 2 Ethibond sutures, SMC, SP, and Weston knots required at least three additional half-hitches before knot security plateaued. However, when the first half-hitch was switched to the loop limb of the sliding knot, only two additional half-hitches (2 s-RHAPs) were required to reach maximum knot security. Using No. 1 PDSII sutures, SMC knots needed one additional half-hitch to reach maximum knot security, whereas SP and Weston knots required two half-hitches. However, SMC, SP and Weston knots with switched first half-hitch only required one additional half-hitch (1 s-RHAP) to achieve maximum knot security. This study demonstrated that switching the post just after the sliding knot could save one half-hitch without compromising knot security. That means that sliding knots with 2 s-RHAPs for No. 2 Ethibond and 1 s-RHAPs for No. 1 PDSII achieved knot security comparable to that of sliding knots with 3 c-RHAPs and with 2 c-RHAPs, respectively. The results suggested that the optimized configuration for arthroscopic sliding knots required a secure sliding knot, such as, the SMC, SP, or Weston knots and 2 s-RHAPs when No. 2 Ethibond or No. 1 PDSII suture materials were used considering the unraveling tendency of No. 1 PDSII. Results of the current study may be helpful for establishing arthroscopic sliding knot-tying routines for best results in clinical practice.
Keywords: SLIP KNOT; LOOP SECURITY; LOCKING MECHANISM; SUTURE; MONOFILAMENT